Enhancement of the thermoelectric performance of bulk SnTe alloys via the synergistic effect of band structure modification and chemical bond softening. Issue 27 (26th June 2017) - Wang, Hongchao; Hwang, Junphil; Zhang, Chao; Wang, Teng; Su, Wenbin; Kim, Hoon; Kim, Jungwon; Zhai, Jinze; Wang, Xue; Park, Hwanjoo; Kim, Woochul; Wang, Chunlei
Abstract : Seebeck coefficient of SnTe is largely enhanced by large band effective mass or decrease of energy separation through synergistic effect including resonance level and band convergence. Abstract : SnTe alloys, which have the same crystal structure as PbTe, have attracted increasing attention. Here, we demonstrate that the synergistic effect of band structure modification and chemical bond softening can be realized simultaneously in In & Mn doped SnTe bulk alloys. The Seebeck coefficient and power factor are synergistically improved by co-doping of In and Mn. In doping is known to introduce a resonance level. Mn doping reduces the separation of light- and heavy-valence bands. The combination of these effects significantly enhances the Seebeck coefficient at room temperature owing to around a factor of five times increase in the band effective mass. The reduction of thermal conductivity is from the decrease of both the electronic and phononic parts. The electronic thermal conductivity is decreased by the increase in defect scattering, as can be confirmed by the carrier mobility. The force constant of the bonds around the Te site is decreased due to the co-doping of In & Mn, which indicates that the chemical bonds are softened, which leads to low sound velocity and lower lattice thermal conductivity. As a result, the peak thermoelectric figure of merit, zT = 1.03 has been achieved for Sn0.89 In0.01 Mn0.1 Te at 923 K. This strategy of using the synergistic effect of band structure modification and chemical bond softening could be applicable to other thermoelectric materials.